Voyage - Baxter, Stephen (New York, N.Y. : HarperPrism, 1997)
An alternate history in which the American space program continues unabated after the 1969 moon landing, and pursues a course that leads to a manned mission to Mars.
Publisher's Weekly.
Wilson's Fiction.
Adult
Keywords: Space flight -- Fiction; Alternative histories; Imaginary voyages; Science fiction; United States -- History -- 1969- -- Fiction; United States -- History -- Fiction; Alternative histories; Science fiction